2020
DOI: 10.1080/20002297.2020.1832832
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus rhamnosus strains of oral and vaginal origin show strong antifungal activity in vitro

Abstract: Background: Intake of probiotic bacteria may prevent oral Candida infection. Objective: To screen the antifungal activity of 14 Lactobacillus candidate strains of human origin, against six opportunistic C. albicans and non-albicans species. A second aim was to study the acid production of the four strains showing the strongest antifungal activity. Methods: We used an agar overlay growth inhibition assay to the assess the antifungal activity of the lactobacilli. The acid-producing capacity was measured with pH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
(66 reference statements)
0
5
0
1
Order By: Relevance
“…In our study, L. plantarum (DSM 20174) and L. Casei showed a weak and/or no anti-Candida activity against C. albicans isolates tested. However, other studies have been established the anti-Candida activity of both species 50,51 Our results can be explained by antimicrobial activity of lactobacilli is strain dependent 52 .…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In our study, L. plantarum (DSM 20174) and L. Casei showed a weak and/or no anti-Candida activity against C. albicans isolates tested. However, other studies have been established the anti-Candida activity of both species 50,51 Our results can be explained by antimicrobial activity of lactobacilli is strain dependent 52 .…”
Section: Discussionmentioning
confidence: 57%
“…We choosed L. rhamnosus ATCC 7469 for subsequent experiment as it exhibited potent activity against majority of C. albicans isolates. Recent study by Rose Jørgensen et al reported that L. rhamnosus strains exhibited the best growth inhibition activity among tested strains against candida spp 52 .…”
Section: Discussionmentioning
confidence: 99%
“… 65 In studies, the best inhibitory effect of lactobacilli strains on Candida growth is associated with the highest organic acid production. 62 By acidifying the environment, lactic and acetic acids seem to be able to significantly prevent Candida spp . growth and therefore pathology onset.…”
Section: Effects Of Vaginal Bacterial Organic Acids On Cand...mentioning
confidence: 99%
“…suggested that a low pH prevents C. albicans from undergoing the yeast-hyphal transition, leading to energy consumption, growth inhibition and cell death. 62 When chronically exposed to acidic stress, C. albicans exhibits a transcriptional shift, notably in iron homeostasis-involved genes. Interestingly, Cottier et al .…”
Section: Effects Of Vaginal Bacterial Organic Acids On Cand...mentioning
confidence: 99%
“…Noutro estudo, dois isolados orais, L. rhamnosus DS32992 e DSM32991 foram os que mostraram ser os mais ativos contra células planctónicas de Candida spp. [5]. Conclusões: A microbiota oral parece ser uma fonte de bactérias do ácido láctico com atividade contra agentes causadores de candidíase oral.…”
Section: R E S U M O S D a S C O M U N I C A ç õ E S E M P O S T E Runclassified